Karakteristik jerapan fosfat ‘kleinano’ terseparasi dari tuf volkan Indonesia - Untung Sudadi; Muhammad Anggi Imaduddin; Iskandar Iskandar (Graduate School Bogor Agricultural University (SPs IPB), 2022)
From an Indonesian volcanic tuff taken from parent material layer of an Andisols profile, it was separated ‘nanoclay’ fraction of <200 nm particle size. The separated ‘nanoclay’ exhibits pH-dependent charge characteristic due to the presence of allophane in the tuff. Therefore, it can be utilized as a natural anionic adsorbent since its separation process was conditioned to proceed at pH <4.0. This study aims to compare phosphate adsorption characteristics of positively charged ‘nanoclay’ based on Langmuir, Freundlich, Brunauer-Emmett-Teller (BET), and Dubinin-Radushkevich (D‒R) isothermal models. The ‘nanoclay’ was separated using US Patent No. US2010/0187474 A1 procedure that was modified in this study with addition of HCl treatment. The results showed that after 48 h equilibration, application of Langmuir and D‒R model resulted adsorption capacity (qe para-meter) of 460.78 (two-sites) and 439.66 mg.g-1 (heterogeneous sites), respectively, while BET and Freundlich model resulted respectively adsorption at the first adsorptive layer (qmono parameter) of 111.11 mg.g-1 (multilayers) and adsorption constant (1/n parameter) of 0.28. The later indicated that the studied ‘nanoclay’ was a high-quality adsorbent (1/n value 0.1-0.5). Limitations and advantages application of each model were discussed. However, Langmuir showed the best performance in term of linear equations with the highest R2 values obtained.